2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00753
|View full text |Cite
|
Sign up to set email alerts
|

Domain-Specific Batch Normalization for Unsupervised Domain Adaptation

Abstract: We propose a novel unsupervised domain adaptation framework based on domain-specific batch normalization in deep neural networks. We aim to adapt to both domains by specializing batch normalization layers in convolutional neural networks while allowing them to share all other model parameters, which is realized by a twostage algorithm. In the first stage, we estimate pseudolabels for the examples in the target domain using an external unsupervised domain adaptation algorithm-for example, MSTN [27] or CPUA [14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
279
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(280 citation statements)
references
References 16 publications
1
279
0
Order By: Relevance
“…To adapt a brain segmentation network to a new modality, Karani et al [20] observed that fine-tuning the BN layers on the new modality while fixing other CNN weights was helpful to preserve the cross-site shared information. Similarly, Chang et al [22] observed that independently normalizing features from different domains produced competitive performance under the setting of domain adaptation, which could demonstrate the effectiveness of independent feature normalization for handling domain shift problem.…”
Section: Related Work a Multi-site Learningmentioning
confidence: 84%
“…To adapt a brain segmentation network to a new modality, Karani et al [20] observed that fine-tuning the BN layers on the new modality while fixing other CNN weights was helpful to preserve the cross-site shared information. Similarly, Chang et al [22] observed that independently normalizing features from different domains produced competitive performance under the setting of domain adaptation, which could demonstrate the effectiveness of independent feature normalization for handling domain shift problem.…”
Section: Related Work a Multi-site Learningmentioning
confidence: 84%
“…As the performance of DA methods is tightly linked to the network architectures, some works begin to design domainspecialized architectures that process the source and target data separately. Chang et al present domain-specific batch normalization (DSBN) [54] to learn domain-specific information for each domain separately. Later on, Carlucci et al [55] introduce novel domain alignment layers (DAlayers), which automatically learn the degree of good alignment at different levels of the network.…”
Section: Domain-specialized Architecture Based Methodsmentioning
confidence: 99%
“…During testing phase, the estimated values cannot accurately represent the testing data statistics in each site and hence will lead to performance degradation. In this paper, we employ the domainspecific batch normalization (DSBN) method [9], [33], [34] by assigning an individual BN layer for each site independently to explicitly tackle the statistic discrepancy. As shown in Fig.…”
Section: ) Separate Batch Normalization At Data Heterogeneitymentioning
confidence: 99%